Firm-level heterogeneity and the decision to export: A real option approach - Wim A. Naudé; Thomas Gries; Natasa Bilkic (Institute for the Study of Labor (IZA), 2013)
In new new international trade theory, whether firms export or not are determined by their productivity. These models assume that firms enter a market to find their productivity levels revealed to them as in a lottery. In this paper we propose an alternative way to model whether firms export or not, namely as a firm-level decision akin to an investment decision with a real option value. We show that endogenizing the export decision is consistent with patterns of productivity and exporting reported in the empirical literature.
Keywords: D92; D81; L26; M13; 330; international new ventures; firm-level heterogeneity; start-ups; stochastic dynamic programming; trade; exports; productivity; real option theory; investment; firms; international entrepreneurship